2021
DOI: 10.1109/jsen.2020.3020889
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent and Optimal Resource Allocation Approach in Sensor Networks for Smart Agri-IoT

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research.-You may not further distribute the material or use it for any profit-making activity or commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…These methods perform badly when dealing with rapidly changing data. The authors of [9] developed a dual prediction-based data reduction technique.…”
Section: Related Workmentioning
confidence: 99%
“…These methods perform badly when dealing with rapidly changing data. The authors of [9] developed a dual prediction-based data reduction technique.…”
Section: Related Workmentioning
confidence: 99%
“…In [184], the authors indicated SF has the ability to deliver sustainability and beneficial production, which is founded on inventive technology, such as IoT. Sensor-based SF frameworks to offer an attractive solution for the farmer were presented in [185]. The work in [186] proposed IoT advancements can diminish the expense of labor cost, reduce the human effort and enhance the scale of sensor-based farming system by information assortment from sensors.…”
Section: Iot Based Smart Farming Sensor Systemsmentioning
confidence: 99%
“…To this end, there has been an increase in the number of works applying MARL to RRM in different types of wireless systems, e.g., unmanned aerial vehicle (UAV) communication [11], multi-user cellular systems [14], Industry 4.0 device-to-device communication [15], multibeam satellite systems [16], integrated access and backhaul networks [17], non-orthogonal multiple access [18], multi-cell networks [19], and joint scheduling of enhanced mobile broadband and URLLC in 5th generation (5G) systems [20]. Other studies have applied RL to wireless resource allocation in sensor networks for smart agriculture [21], smart ocean federated learning-based IoT networks [15], and distributed antenna systems [22].…”
Section: Introductionmentioning
confidence: 99%